Reducing Non‐Radiative Voltage Losses by Methylation of Push–Pull Molecular Donors in Organic Solar Cells. Issue 17 (29th June 2021) - Baisinger, Lukasz; Andrés Castán, José María; Simón Marqués, Pablo; Londi, Giacomo; Göhler, Clemens; Deibel, Carsten; Beljonne, David; Cabanetos, Clément; Blanchard, Philippe; Benduhn, Johannes; Spoltore, Donato; Leo, Karl
Abstract: Organic solar cells are approaching power conversion efficiencies of other thin‐film technologies. However, in order to become truly market competitive, the still substantial voltage losses need to be reduced. Here, the synthesis and characterization of four novel arylamine‐based push‐pull molecular donors was described, two of them exhibiting a methyl group at the para ‐position of the external phenyl ring of the arylamine block. Assessing the charge‐transfer state properties and the effects of methylation on the open‐circuit voltage of the device showed that devices based on methylated versions of the molecular donors exhibited reduced voltage losses due to decreased non‐radiative recombination. Modelling suggested that methylation resulted in a tighter interaction between donor and acceptor molecules, turning into a larger oscillator strength to the charge‐transfer states, thereby ensuing reduced non‐radiative decay rates. Abstract : Structural tuning improves efficiency : Modification of the molecular structure of organic molecules allows to influence the performance of organic photovoltaic devices. Addition of a methyl group in the para ‐position of the external phenyl ring leads to increase in open‐circuit voltage. Quantum‐chemical calculations attribute this effect to the increase of the oscillator strength of the electronic transition between the donor and acceptor.